Pessoas normais, de Sally Rooney : um romance de formação no século XXI - Paz, Mauro Athayde (2023)
This dissertation aims to analyze Sally Rooney's Normal People (2018) from the perspective of Bildungsroman (novel of formation). To establish the key characteristics of this subgenre, I review the studies of Karl Morgenstern, Georg Wilhelm Friedrich Hegel, Georg Lukács, Mikhail Bakhtin and Franco Moretti. I also examine how the Bildungsroman have been developed in Irish literature. The novel's analysis is based on the examination of the narrative elements (character, space, time, narrator and plot) to determine the social tensions of the 21st century that arise in Normal People and influence the formative paths of the protagonists Connell and Marianne.